Effect of breast-conserving surgery and modified radical mastectomy on operation index, symptom checklist-90 score and prognosis in patients with early breast cancer. Issue 11 (March 2020) - Qiu, Han; Xu, Wen-Hui; Kong, Jun; Ding, Xiao-Jun; Chen, Deng-Feng
Abstract : Abstract: The present study aims to analyze the effects of breast-conserving surgery and modified radical mastectomy on operation indexes, Symptom checklist-90 scores and prognosis in patients with early breast cancer. The clinical data of 128 patients with breast cancer who were treated in our hospital from May 2015 to May 2016 were included into the analysis. These patients were divided into 2 groups, according to the different modes of operation (n = 64): control group, patients underwent modified radical mastectomy; observation group, patients underwent early breast conserving surgery. Then, the surgical indexes and prognosis were compared between these 2 groups. Intraoperative bleeding volume, incision length and hospitalization duration were better in the observation group than in the control group ( P  < .05). Furthermore, postoperative symptom checklist-90 scores in the observation group were better than scores before the operation, and were better than the scores in the control group ( P  < .05). Moreover, the incidence of postoperative complications was lower in the observation group (3.13%) than in the control group (21.88%, P  < .05). Early breast-conserving surgery is more advantageous for breast cancers and results to lesser bleeding, rapid recovery, and fewer complications.